A study on longitudinal motion stability of a variable-structure SWATH USV with and without twin hydrofoils. (1st December 2022) - Wang, Jiandong; Zhuang, Jiayuan; Su, Yumin
Abstract: The form-changeable unmanned surface vehicle (USV) have a high research enthusiasm due to its far-ranging applicability, strong combat capability and low operating cost. This paper constructs a variable-structure Small Waterplane Area Twin Hull (SWATH) USV with twin hydrofoils, and aims at assessing its longitudinal motion stability (LMS) in the catamaran-form state (CFS) by parametric model and CFD method. The parametric representation of the torpedo, double struts and hydrofoils was conducted by uniform B-spline curves, 3-D coordinates conversion and surface generation method. The CFD code was verified, and used to calculate the LMS of the vessel with different strut configurations, form-states and CG position. Based on numerical results, the causes of different instability behaviors were expounded. Further, the LMS of the models with and without hydrofoils was compared at F r  = 0.1–0.8, the adjustment method of fore and aft hydrofoils to sailing attitudes was explained, the rational allocation of attack angles was also offered. The results show that the slender double struts arranged at both ends of torpedo is more conducive to the LMS and resistance, the vessel should sail in the CFS of γ s  ≤ 10° at F r  > 0.6; the hydrofoils slightly weakens the LMS at low F r, makes the bow appear slight updip at F r  = 0.4–0.6, but still can sails stably; adjusting attack angles can inhibit the instability, and the most effective allocation of the fore and aft hydrofoil's attack angles is linearly arranged at F r  = 0.7, 0.8, also the adjusting can reduce the upward trim at F r  = 0.9, 1.0, but the hull is lifted higher and arises the bow updip due to the free surface suction force, at this time, the attack angle's graduation should be refined to realize the finer adjustment to the dynamic trim. Highlights: A form-changeable SWATH USV with twin hydrofoils is designed, and the longitudinal motion stability of its catamaran-form state (CFS) is investigated by the CFD method. Parametric modeling of the form-changeable CFS model with different double struts is established by uniform B-spline curves, 3-D coordinates conversion, surface generation method. The different instability behaviors of the CFS models with different struts, form-states are analysed by the captured flow details and hydrodynamic pressure nephogram. The adjustment method of fore and aft hydrofoils to sailing attitudes is studied, also the rational allocation on attack angles to inhibit the instability is offered.